Interpreting employability in the veterinary context : a guide and framework for veterinary educators. - Cake, Martin; Bell, Melinda; Cobb, Kate; Feakes, Adele; Hamood, Wendy; Hughes, Kirsty; King, Eva; King, Laura; Mansfield, Caroline; McArthur, Michelle; Matthew, Susan; Mossop, Liz; et al. (Australia. Dept of Education and Training (DET), 2018)
The aim of this work is to provide guidance on how to interpret and apply the construct of employability in the context of veterinary education and policy. Since employability has scarcely been examined in the veterinary context despite its emerging importance in higher education, this guide is intended to assist veterinary schools in developing evidence-based employability approaches with an authentic veterinary 'flavour'. It is also intended to provide guidance for accreditors and policy makers, in aligning outcomes towards the capabilities most important to professional success and satisfaction. Although employability is best approached as a whole–of–career construct, this guide is primarily focused on graduate-level outcomes informing undergraduate pedagogy supporting transition to practice. However we hope that other parts of the profession may benefit from a clearer understanding of veterinary employability, as the basis for professional, organisational, and individual success. [Aims and Scope, ed]